2022
DOI: 10.1021/acsanm.2c03723
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Insights of Ti-Based MXenes Thermal Decomposition and Transformation to Carbon-Supported Ti–O Phases for Energy Applications

Abstract: Ti–O phases combined with carbon materials are attractive for applications in energy storage, photocatalysis, and gas sensing. The oxidation of Ti-based MXenes at high temperatures has been proposed as an effective synthesis method for carbon-supported anatase and rutile TiO2. Here, the thermal degradation and phase transformation of Ti3C2T2 (T = O or OH) under vacuum, air, and water vapor environments are investigated using reactive molecular dynamics simulations. Ti3C2(OH)2 is most stable under vacuum and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The calculation results show that Ti 3 C 2 (OH) 2 /O 2 system has an identical oxidation behavior with Ti 3 C 2 O 2 /O 2 system (Figures S15 and S16). The F surface groups are not taken in the work due to the fact that the parameterized F surface groups are not available in the current force fields 33 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculation results show that Ti 3 C 2 (OH) 2 /O 2 system has an identical oxidation behavior with Ti 3 C 2 O 2 /O 2 system (Figures S15 and S16). The F surface groups are not taken in the work due to the fact that the parameterized F surface groups are not available in the current force fields 33 …”
Section: Resultsmentioning
confidence: 99%
“…The F surface groups are not taken in the work due to the fact that the parameterized F surface groups are not available in the current force fields. 33…”
Section: Nature Of the Surfaces Of Different Crystal Planesmentioning
confidence: 99%
“…Ti/C/O parameters were optimized against Ti-C bond, C-Ti-C, and C-Ti-O angle distortions and the energy of condensed phases. MX-2016 [36] was employed in [35,37,81,178,[186][187][188][189][190] for ReaxFF simulations.…”
Section: Reaxff Parameter Set Parameter Optimizationmentioning
confidence: 99%
“…It was clearly shown that as the oxidation proceeds under controlled temperature, Ti atoms migrate to the MXene surface, forming carbon-supported titania (figure 12(e)). The crystal phase of titania was further investigated by Badawy et al [189]. In dry air, anatase and rutile TiO 2 were formed on Ti 3 C 2 T 2 (T=O, OH) MXene, whereas rock-salt TiO was formed under vacuum.…”
Section: Surface Chemistrymentioning
confidence: 99%
“…[35] Several studies have demonstrated how further oxidation severely destroys the integrity of the MXene structure, thereby limiting its lifetime in service and precluding many useful applications due to a decrease in the properties of interest. [36][37][38][39] Although efforts have been made to understand the details of their evolving chemistry during oxidation, [40,41] some questions are still unanswered, such as the role of non-O surface terminations, intercalants, or impurities from synthesis. Designing MXenes with improved oxidation resistance is therefore extremely challenging, and for this reason the improvement of chemical and temperature stability of MXenes is considered in the community to be one of the research challenges of this decade.…”
Section: Introductionmentioning
confidence: 99%